2014
DOI: 10.3390/ijms15045838
|View full text |Cite
|
Sign up to set email alerts
|

Cetuximab-Induced MET Activation Acts as a Novel Resistance Mechanism in Colon Cancer Cells

Abstract: Aberrant MET expression and hepatocyte growth factor (HGF) signaling are implicated in promoting resistance to targeted agents; however, the induced MET activation by epidermal growth factor receptor (EGFR) inhibitors mediating resistance to targeted therapy remains elusive. In this study, we identified that cetuximab-induced MET activation contributed to cetuximab resistance in Caco-2 colon cancer cells. MET inhibition or knockdown sensitized Caco-2 cells to cetuximab-mediated growth inhibition. Additionally,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
36
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 34 publications
(38 citation statements)
references
References 26 publications
2
36
0
Order By: Relevance
“…It is well established that c-Src and EGFR phosphorylate each other in a positive feedback loop 25,26. Our previous study showed that c-Src activation mediated cetuximab resistance in colon cancer cells,14 which have not been confirmed in GC yet. Moreover, our study showed that c-Src was activated by RANKL in the migration of breast cancer cells 13.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…It is well established that c-Src and EGFR phosphorylate each other in a positive feedback loop 25,26. Our previous study showed that c-Src activation mediated cetuximab resistance in colon cancer cells,14 which have not been confirmed in GC yet. Moreover, our study showed that c-Src was activated by RANKL in the migration of breast cancer cells 13.…”
Section: Discussionmentioning
confidence: 92%
“…Western blot was performed as previously described 14. The following antibodies were used: Anti-RANK antibody was obtained from Bethyl Laboratories, Inc. (Montgomery, TX, USA).…”
Section: Methodsmentioning
confidence: 99%
“…HGF is the ligand for the MET receptor and can activate many of the same signaling pathways as EGFR. Furthermore, dysregulated MET signaling has been linked to HNSCC [41] and is a known mechanism of resistance to EGFR inhibitors [12,42]. Baseline serum IL6 levels were highly correlated with baseline HGF levels, suggesting a potential interaction between the IL6 pathway and the HGF/MET pathway in HNSCC.…”
Section: Discussionmentioning
confidence: 99%
“…Recent evidence indicates the MET signaling pathway may play an important role in CRC growth and metastasis, 26,32,33 is associated with more advanced metastatic disease and tumor stage, 34,35 and may mediate resistance to EGFR inhibitors. 36,37 Dual MET and EGFR blockade could potentially provide more durable clinical benefit in mCRC, which led to the investigation of new MET-targeting agents, including tivantinib. Preclinical findings suggest that tivantinib may also affect the cytoskeleton, and recent studies show this may happen via MET and paxillin inhibition.…”
Section: Discussionmentioning
confidence: 99%